MEMBANGUN KEADILAN RESTORATIF BAGI SI MISKIN - Umar Sholahudin (Jurnal Sejarah dan Budaya, 2013)
Abstract. The poor are those who do not have the empowerment of social, political, economic and legal access. Poor people didn’t know and less understood the positive law of the State. It needs juridical and sociological wisdom in resolving the legal case that afflicts the poor. Legal cases was hit the poor or weak should not be resolved through a process of positive law, but enough to be completed at the community level through peaceful means and deliberation. Completion gives more sociological sense of justice for the poor. This settlement, known as the principle of restorative justice, in example justice outside the court obtained a positive law, through the recovery process with a spirit of mutual forgiveness between perpetrators and victims. Applying the law against the poor, it's time we not only understand and apply the law of the legalistic-positivistic, but need to do a groundbreaking law that is more progressive and responsive, which is trying to get out of the shackles or prison law is positivistic and legalistic Law that responds to social needs of society.